2016
DOI: 10.1016/s0140-6736(15)00067-7
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis

Abstract: В представленном обзоре отмечено изменение эпидемиологического про-филя инфекционного эндокардита (ИЭ) с увеличением заболеваемости в пожилом возрасте. Обсуждаются факторы риска ИЭ, включая перенесен-ные ранее заболевания эндокарда различного генеза, имплантацию искус-ственного клапана, проведение различных лечебных и диагностических инвазивных процедур и особенно кардиохирургических вмешательств. Среди факторов риска, предрасполагающих к инфекционному поражению эндокарда у пожилых лиц, отмечены кальцификация … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
687
8
86

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 787 publications
(891 citation statements)
references
References 145 publications
12
687
8
86
Order By: Relevance
“…1,2,18 Advances in medical technology, increased indwelling intravascular device use and increased prevalence of comorbidities such as end-stage renal disease contribute to this burden. 33 Two LMIC studies reported on the site of acquisition of IE. Simsek-Yavuz et al 21 characterized 23% of IE cases as HAIE at a referral centre in Turkey, while Damasco et al 34 reported predominantly HAIE (56%) in two centres in Brazil.…”
Section: Place Of Infection Acquisitionmentioning
confidence: 99%
“…1,2,18 Advances in medical technology, increased indwelling intravascular device use and increased prevalence of comorbidities such as end-stage renal disease contribute to this burden. 33 Two LMIC studies reported on the site of acquisition of IE. Simsek-Yavuz et al 21 characterized 23% of IE cases as HAIE at a referral centre in Turkey, while Damasco et al 34 reported predominantly HAIE (56%) in two centres in Brazil.…”
Section: Place Of Infection Acquisitionmentioning
confidence: 99%
“…Around 80%‐90% of IE cases result from staphylococcal, streptococcal, and enterococcal infection 8, 910…”
Section: Discussionmentioning
confidence: 99%
“…1 The concept that invasive dental procedures could cause IE was first suggested in 1923. 2 With the advent of antibiotics, the idea developed that antibiotic prophylaxis could be used before invasive dental procedures to reduce the risk of IE in susceptible individuals.…”
Section: Guidelines On Prophylaxis To Prevent Infective Endocarditis mentioning
confidence: 99%